A dynamic model for organic waste management in Quebec (D-MOWIQ) as a tool to review environmental, societal and economic perspectives of a waste management policy. (August 2017) - Hénault-Ethier, Louise; Martin, Jean-Philippe; Housset, Johann
Graphical abstract: Highlights: A dynamic systems model for organic waste management policy impact was created. Current policy goals (diversion rate and OW landfill ban) are favorable. Business as usual scenario favors OW landfilling. Infrastructure investments and awareness favor more alternative OW treatment. Incentive taxes boost valorization better than massive infrastructure investments. Abstract: A dynamic systems model of organic waste management for the province of Quebec, Canada, was built. Six distinct modules taking into account social, economical and environmental issues and perspectives were included. Five scenarios were designed and tested to identify the potential consequences of different governmental and demographic combinations of decisions over time. Among these scenarios, one examines Quebec's organic waste management policy (2011–2015), while the other scenarios represent business as usual or emphasize ecology, economy or social benefits in the decision-making process. Model outputs suggest that the current governmental policy should yield favorable environmental benefits, energy production and waste valorization. The projections stemming from the current policy action plan approach the benefits gained by another scenario emphasizing the environmental aspects in the decision-making process. As expected, without the current policy and action plan in place, or business as usual, little improvements are expected in waste management compared to current trends, and strictly emphasizing economic imperatives does not favor sustainable organic waste management.